Perlindungan Hukum terhadap Hak-Hak Pekerja sebagai Wujud dalam Bela Negara Menurut Undang-Undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan - Satino Satino; Citraresmi Widoretno Putri; Dwi Desi Yayi Tarina; Kayus Kayowuan Lewoleba; Yuliana Yuli Wahyuningsih (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2026)
National defense is not only related to military defense, but also encompasses the active role of citizens in maintaining social and economic stability. Workers are a vital element in national development. Therefore, protecting workers' rights is an integral part of national defense efforts. This article aims to analyze the legal protection of workers' rights under Law Number 13 of 2003 concerning Manpower and relate it to the values ​​of national defense. The method used is a normative juridical approach through literature review. The results of the study indicate that labor regulations have regulated various workers' rights, but implementation challenges in the field remain high. The active role of all parties is needed to ensure legal protection is truly realized as a form of civil national defense. This indicates that legal protection for workers needs to be strengthened through the active roles of the government, employers, and workers themselves to create social and economic stability, which is an integral part of national defense. Therefore, an active role is needed from all parties, including the government, employers, and workers themselves, to realize optimal legal protection as a form of civil national defense that supports the sustainability of national development.